Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
The answer: ( 2 , -3 )
Step-by-step explanation:
equation (1): 5x + 2y = 4
equation (2): y = x - 5
step1: sub ( x-5 ) for y in equation 1:
5x + 2 ( x-5 ) = 4
step2: multiply 2 by the bracket:
5x + 2x - 10 =4
step3: add the x term together:
7x - 10 = 4
step4: add 10 for both sides:
7x = 14
step5: divide by 7 from both sides to get the value of x:
x = 2
step6: sub ( 2 ) for x in equation 2 :
y = x - 5
y = 2 - 5
step7: simplify to get the value of y:
y = -3
So the answer is:
x = 2 and y = -3
( 2 , -3 )
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.